(3TQM GdfZeGJ hYdhgG hgHhWgGs - (3eLghds
(3ChdgG (B:s
(3GYde CjgG GdWGdH Gf eTGjN gPg GdYdhe PcQhG Cf GdfZe dg Ydh hCh Cf ShGO s
(3BNQgG (B:s
(3agPg GdCUhd hGdaQhY heGjJYdb HTQM gPg GdEKfi YTQ hGdSJg s
(3TQM ajg GdCfZGe GdGKfi YTQ hGdChRGf GdSJIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQ a YGeg (B- (3U (B64 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjg eUhQI Yf CMeO GdKGdK (B((3afhf LejdI (B510) s
Keywords: (3GdehSjbi hGdZfGAs